KUHAP SEBAGAI SARANA MEWUJUDKAN SISTEM PERADILAN PIDANA TERPADU DAN KENDALANYA - -, Supriyanta - (RESPONSA, 2009)
The Mechanism Criminal Procedure Law had been designed as a criminaljustice with a system approach, however,systematically there are severalweaknesses in its regulation to the existence of criminal justice system. Theweaknesses are especially concerning the regulation in the subsystem ofinvestigation and coordinative relation beetween the subsystem ofinvestigation and prosecution.Keywords : Criminal Procedure Law, criminal justice system